Cyanide concentration of fried cassava chips and its effect on chip taste - Almazan, A.M. (1986)
Fried chips prepared from cassava tuber or flour are consumed as snack in some Asian countries such as India, Indonesia, Malaysia and the Philippines. Chips made from fresh tubers were similar to potato chips and contained safe levels of cyanide, if low-cyanide varieties were used. Those processed from flour, often called Kroepeck, also contained minimal cyanide if the flour was obtained from low-cyanide clones. The colour and taste of Kroepeck also depended on the cassava variety.